2017
DOI: 10.1002/mame.201600507
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Highly Aligned Nanowire Printing

Abstract: Nanowires (NWs) are 1D confined nanostructures; this geometry gives them unique properties that have been exploited in fabrication of high-density and high-tech electronic devices. Current method to produce NWs cannot fabricate largescale-aligned NW arrays with precise control of length, orientation, location, and number of NWs individually; these inabilities hinder application of NWs in practical electronics. This paper describes e-nanowire printing, a method to print highly aligned NWs on a large scale, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 66 publications
(208 reference statements)
0
21
0
Order By: Relevance
“…However, when subjected to practical applications, traditional polymer in most of these sensors will be broken, the AgNWs conductive network will then be subsequently destroyed. If the AgNWs were not interconnected, the sensors would not transmit signal any more . Thus, an ideal flexible strain sensor should not only retain high flexibility, but also could be rapidly healed after mechanical damage …”
Section: Introductionmentioning
confidence: 99%
“…However, when subjected to practical applications, traditional polymer in most of these sensors will be broken, the AgNWs conductive network will then be subsequently destroyed. If the AgNWs were not interconnected, the sensors would not transmit signal any more . Thus, an ideal flexible strain sensor should not only retain high flexibility, but also could be rapidly healed after mechanical damage …”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively low electrical conductivity of large‐scale graphene and high contact resistance of carbon nanotubes, the applications of these carbon‐based nanomaterials are highly limited. And further on the poor conductivity and instability of conducting polymers, MNEs are a strong candidate due to their superior electrical and optical performance …”
Section: Introductionmentioning
confidence: 99%
“…Under the stretching of collector speed, an EDW jet can be deposited to print orderly straight lines, which has attracted lots of interests from researchers [ 10 , 11 , 12 , 13 ]. Bu et al [ 14 ] reported the method of mechano-electrospinning (MES) with the help of a mechanical drawing force for high-speed collectors to direct-write oriented nanofiber with high deposition accuracy.…”
Section: Introductionmentioning
confidence: 99%